PENGARUH MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PT INDOFOOD - Nurul Fazira Nasution; Nabila Farah Dhiba; Ilfa Damayanti Andini Harahap; Dwita Agustina Putri; Arsyadona Arsyadona (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article discusses the influence of risk management on the financial performance of PT Indofood. In an increasingly complex business world, risk management has become an important aspect that companies must pay attention to in order to maintain stability and growth. The findings indicate that the effective implementation of risk management positively contributes to the financial performance of PT Indofood, as reflected in increased profitability and operational efficiency. This finding emphasizes the importance of risk management strategies in supporting the sustainability and competitiveness of the company in a dynamic market.